Relationships Between Phenotype and Function of Blood CD4+ T-Cells and Ascending Thoracic Aortic Aneurysm: an Experimental Study - Sbrana,Silverio (2019)
Abstract Introduction: Non-familial ascending thoracic aorta dilation and aneurysms (TAAs) are silent diseases in elderly patients. Histopathology revealed that functionally polarized infiltrating CD4+ T-cells play a key role in aortic wall weakening. Objective: To evaluate the possible associations between phenotype and cytokine production of circulating CD4+ T-lymphocytes and the presence of TAA in patients with aortic valve disease (AVD). Methods: We studied blood samples from 10 patients with TAA and 10 patients with AVD. Flow cytometry was used to quantify: a) CD4+ T-lymphocytes surface expression of CD25, CD28, and chemokine receptors (CCR5, CXCR3, CX3CR1); b) fractions of in vitro stimulated CD4+ T-cells producing cytokines (interferon gamma [IFN-γ], interleukin [IL]-17A, IL-21, IL-10); c) CD4+CD25highFoxP3+ regulatory T-cells (Treg) fraction. Enzyme-linked immunosorbent assays (ELISA) were performed for cytokines (IFN-γ, IL-6, IL-10, IL-17A, IL-23, transforming growth factor beta [TGF-β]) and chemokines (RANTES, CX3CL1). Results: The total CD4+CD28±CD4+/CX3CR1+ T-cells fraction was higher (P=0.0323) in AVD (20.452±4.673) than in TAA patients (8.633±2.030). The frequency ratio of CD4+ T-lymphocytes producing IFN-γ vs. IL-17A+IL-21 cytokine-producing CD4+ T-cells was higher (P=0.0239) in AVD (2.102±0.272) than in TAA (1.365±0.123) patients. The sum of CD4+CD28±CD4+/CX3CR1+ T-cells correlated positively with values of the previous cytokine ratio (P=0.0002, R=0.732). The ratio of CD4+CD28±CD4+/CX3CR1+ T-cells vs. Treg was higher (P=0.0008) in AVD (20.859±3.393) than in TAA (6.367±1.277) patients. Conclusion: Our results show that the presence of TAA in subjects with AVD is associated with imbalance between phenotypic and cytokine-producing subsets of circulating CD4+ T-lymphocytes, prevalently oriented towards a pro-fibrotic and IFN-γ counteracting effect to functional polarization.